Prachāthammanāthānus̨ōn : phithī phrarātchathān phl̄œngsop Phrakhrū Prachāthammanāt (Ch̄æng Thānangkarō) na prāsāt 9 y̨ōt Wat Rātniyom, ʻ̨Ō. sain̨ōi, Čh̨ō. Nonthaburī, 15 Mīnākhom Ph̨ō.S̨ō. 2541 (Thekprōmōchan ʻ̄æn ʻ̄ædw̄œthaising, 1998)
Cremation volume of a respected Thai monk, Phrakhru Prachathammanat at Wat Ratniyom.